Metode Simple Additive Weighting Dan Weighted Product Dalam Penentuan Peserta Bansos - Alfurqan; Yunus, Mughaffir (Jurnal Sintaks Logika, 2024)
Determining recipients of social assistance in Pinrang Regency requires appropriate methods to ensure fairness and effectiveness. One solution that can be used is a decision support system, which is specifically designed to assist in the decision-making process. This research aims to evaluate and compare simple additive weighting methods and weighted products, which are more effective in determining social assistance recipients. The research method used is quantitative, using the Sensitivity Test as a comparative method. Based on the results of the Sensitivity Test on the Simple Additive Weighting (SAW) and Weighted Product (WP) methods, it can be concluded that the Weighted Product method is more relevant in the context of determining social assistance participants, especially based on criteria. Income and area of residence.